Simulador para estudo avançado da distribuição da dose em bexiga durante procedimentos de braquiterapia ginecológica - Silva, Rogério Matias Vidal da (2015)
Considering the difficulties related to determination the dose delivered on the bladder during procedures of gynecological brachytherapy of high dose rate, this study presents a prototype of a dynamic simulator (phantom) suitable for experimental dosimetry of these organs during this type of procedure. In order to evaluate the phantom´s ability to simulate real clinical situations, a dosimetric study was conducted using radiochromic film and optically stimulated luminescence dosimeters (OSLDs). The phantom was constructed of polymethyl methacrylate (PMMA) and ácido polilático (PLA). Artificial bladders were printed in three dimensions, from computed tomography images (CT) of real patients with brachytherapy applicators already positioned. In the phantom, the artificial bladder can move in all directions. The films and OSLDs were placed on the artificial bladder walls and the applicators were placed according to the original CT image. The prototype phantom simulated the behavior of dose on the surface of each printed bladder. The dosimetric study showed agreement in most cases, with the results obtained from a computerized planning system. In this sense, the methodology presented in this study provides conditions for experimental investigations on the behavior of dose on the surface of the bladder due procedures of intracavitary brachytherapy of cervix.